The Association between Loneliness, Mental Well-Being, and Self-Esteem among Adolescents in Four Nordic Countries - Nelli Lyyra; Einar Baldvin Thorsteinsson; Charli Eriksson; Katrine Rich Madsen; Asko Tolvanen; Petra Löfstedt; Raili Välimaa (International Journal of Environmental Research and Public Health, 2021)
Positive mental health is central to adolescent well-being. The present study examines the prevalence of loneliness and positive mental health indicators (mental well-being and self-esteem) in four Nordic countries and associations between loneliness, mental well-being, and high self-esteem. This study is based on data from the Health Behaviour in School-aged Children (HBSC) study which was conducted in 2018 in Denmark, Finland, Iceland, and Sweden. Participants were 5883 15-year-old boys and girls. To examine the associations between loneliness, mental well-being, and self-esteem, structural equation modeling (SEM) was applied. In the comparison of Nordic countries, the prevalence of loneliness was highest among Finnish and Icelandic adolescents. High mental well-being and high self-esteem were most prevalent in Denmark and Sweden. In general, boys scored higher on positive mental health indicators and girls on loneliness. Loneliness was also a strong indicator of low mental well-being and low self-esteem in all Nordic countries. Loneliness is not only associated with mental health problems such as anxiety and depression, but it is also a risk factor for adolescents’ positive mental health. Positive mental health is important for healthy maturation and there is a need to develop initiatives to reduce adolescent loneliness and so support positive development.